War made easy how presidents & pundits keep spinning us to death - Alper, Loretta; Earp, Jeremy; Media Education Foundation (Northampton, MA : Media Education Foundation, 2007)
Explores how the American news media have disseminated and glamorized the pro-war messages of presidential administrations over the past fifty years.
Based on the book by Norman Solomon.
Title from title screen.
Editor, Andrew Killoy; camera, David Rabinovitz; music, John Van Eps, Leigh Phillips.
Narrated by Sean Penn ; featuring Norman Solomon.
DVD format.
Keywords: Mass media and war -- United States; Wars -- Press coverage -- United States; Government and the press -- United States; Propaganda, American -- United States; United States -- Politics and government -- 20th century